A Study of Channel Member Satisfaction and Ensuing Commitment in International and Domestic Pharmaceutical Distribution Channels - Paul, Reeva (Indian Journal of Marketing, 2014)
Purpose: Giving due cognizance to the importance of satisfaction in the relationship between manufacturers and channel members, this study aims to explore its role in ensuring long term commitment of channel members in the pharmaceutical industry. Moreover, it aims to compare the level of satisfaction in the relationships of distributors with their respective foreign or domestic manufacturers. Design/methodology/approach: A sample of 50 distributors from the pharmaceutical sector was surveyed to put to test the theoretical model proposed between satisfaction and commitment. Multiple regression was used for the analysis. One-way ANOVA was used to compare the levels of satisfaction in the domestic and foreign distribution channels. Findings: The results indicate that the financial dimension of satisfaction, which signifies the attractiveness of the relationship pertaining to matters like margins or return on investment, is the primary factor that drives commitment. In addition, it was found that channel member satisfaction with foreign pharmaceutical manufacturers was significantly higher than it was with domestic manufacturers. Practical Implications: This study recommends that domestic pharmaceutical companies try to take channel relationships to higher levels of collaboration, and attempt to build other dimensions of satisfaction along with the primary financial dimension. Engaging channel members on multiple platforms will build higher commitment as financial motives can easily be usurped by competitors. Indian pharma needs to focus on value added activities like marketing and distribution in order to be globally competitive. Originality/value: The researcher was not able to find any other study exploring channel member relationships in the Indian pharma sector. Hence, this study can be said to be the first of its kind in the Indian pharmaceutical sector.